I am Number Four - Book 1 - Lore, Pittacus (New York : Harper, 2011)
Friendships and a beautiful girl are distracting to a teenager who is hiding on Earth while he waits to develop the powers he will need to rejoin the other six surviving Garde members and fight those who destroyed their planet.
Keywords: Extraterrestrial beings -- Fiction; High schools -- Fiction; Friendship -- Fiction; Moving -- Fiction; Ohio -- Fiction; School stories; Love stories; Movie novels